EFFECT OF BOARD ATTRIBUTES ON ENVIRONMENTAL DISCLOSURE OF LISTED MANUFACTURING FIRMS IN NIGERIA - Obaje Salifu Mamodu; Prof. Muhammad Shehu Tijjani; Dr. Nasiru Yunusa (Gusau Journal of Accounting and Finance, 2025)
The increasing global concern for the environment and the consequent academic interest in researching best environmental disclosure that enhances the quality of reporting had given tremendous drive for this current research. This study examined the effect of board-specific attributes on the environmental disclosure of listed manufacturing firms in Nigeria. The study used the correlational research design with a positivist research paradigm, and agency theory to underpin the relationship between the independent variables and the dependent variable of interest. The population of the study consisted of the 52 listed manufacturing firms on the Nigerian Exchange Group, the population was later reduced to a sample size of 43 manufacturing using the filtration method. Quantitative data were extracted from the audited annual reports of the 43 manufacturing firms used in the study for twelve-year period covering 2011 to 2022. The data were analyzed using the Fixed Effect regression technique. Findings from the study show a significant positive relationship between board size, board gender, board expertise, board independence, and environmental disclosure of listed manufacturing firms in Nigeria. The implication of this result indicate that increase in these variables will lead to a corresponding increase in the environmental disclosure of listed manufacturing firms in Nigeria. Based on the findings of the study, it is recommended that the management of the sampled firms should increase the minimum number of board size to nine members, board independence to about 11.92% of the directors on the board and the minimum number of women on the board should increase to 15.59% as established by the study. This is because it was established by the findings of the study that increase of the various variables as indicated by the descriptive statistics will promote the environmental disclosure among the listed manufacturing firms in Nigeria. Also, the management of the firms should carry out policies that will promote the inclusion of foreign directors on the board as this was also shown to improve the environmental disclosure of manufacturing firms in Nigeria.